A review and recommendations for oral chaperone therapy in adult patients with Fabry disease - Michał Nowicki; Stanisława Bazan-Socha; Beata Błażejewska-Hyżorek; Mariusz M. Kłopotowski; Monika Komar; Mariusz A. Kusztal; Tomasz Liberek; Jolanta Małyszko; Katarzyna Mizia-Stec; Zofia Oko-Sarnowska; Krzysztof Pawlaczyk; Piotr Podolec; et al. (Orphanet Journal of Rare Diseases, 2024)
Abstract Fabry disease (FD) is a rare, X-linked lysosomal storage disorder affecting both males and females caused by genetic abnormalities in the gene encoding the enzyme α-galactosidase A. FD-affected patients represent a highly variable clinical course with first symptoms already appearing in young age. The disease causes a progressive multiple organ dysfunction affecting mostly the heart, kidneys and nervous system, eventually leading to premature death. Disease-specific management of FD includes enzyme replacement therapy with agalsidase α and β or pharmacological oral chaperone migalastat. Migalastat is a low-molecular-mass iminosugar, that reversibly binds to active site of amenable enzyme variants, stabilizing their molecular structure and improving trafficking to the lysosome. Migalastat was approved in the EU in 2016 and is an effective therapy in the estimated 35–50% of all patients with FD with amenable GLA gene variants. This position statement is the first comprehensive review in Central and Eastern Europe of the current role of migalastat in the treatment of FD. The statement provides an overview of the pharmacology of migalastat and summarizes the current evidence from the clinical trial program regarding the safety and efficacy of the drug and its effects on organs typically involved in FD. The position paper also includes a practical guide for clinicians on the optimal selection of patients with FD who will benefit from migalastat treatment, recommendations on the optimal selection of diagnostic tests and the use of tools to identify patients with amenable GLA mutations. Areas for future migalastat clinical research have also been identified.